TEACHER CHALLENGES IN AFFECTIVE ASSESSMENT AT PRIMARY SCHOOL (PIONIR: JURNAL PENDIDIKAN, 2024)
One of the teacher's tasks in affective assessment is to measure students' talents, encouragement and interest in the material being taught. It is hoped that the assessment results will provide an overview of students' affective measures, so that teachers can analyze and make recommendations on how to improve students' attitudes, encouragement and motivation for learning. However, in practice teachers in elementary schools face various challenges in carrying out affective assessments. The method used in this research is a qualitative descriptive analysis method with a phenomenological approach. A phenomenological approach is also used to support literature studies from relevant books and journals. Challenges in affective assessment include teachers' lack of understanding of assessment standards, limitations in implementing authentic assessment, and difficulties in directing and observing students as a whole. The subjectivity of assessment is also a problem, considering that assessment results are often influenced by teachers' personal perceptions and preferences, which causes inconsistent assessment results. Other obstacles include limited assessment tools and methods, lack of training for teachers, and low involvement of parents and the community in supporting affective assessment.Keywords: Teacher Challenges, Affective Assessment, Elementary School
Keywords: Teacher Challenges; Affective Assessment; Elementary School